ArcR contributes to tolerance to fluoroquinolone antibiotics by regulating katA in Staphylococcus aureus - Fu, Tongtong; Fan, Zheng; Li, Yujie; Li, Zhoufei; Du, Bing; Liu, Shiyu; Cui, Xiaohu; Zhang, Rui; Zhao, Hanqing; Feng, Yanling; Xue, Guanhua; Cui, Jinghua; et al. (Frontiers in Microbiology, 2023)
Staphylococcus aureus is an opportunistic pathogen that shows a unique ability to quickly respond to a variety of antibiotics. The Crp/Fnr family transcriptional regulator ArcR controls expression of arginine deiminase pathway genes arcABDC, which enable the utilization of arginine as an energy source for cell growth under anaerobic conditions. However, ArcR shares low overall similarity with other Crp/Fnr family proteins, suggesting that they differ in the response to environmental stress. In this study, we showed that deletion of arcR reduced tolerance of S. aureus to fluoroquinolone antibiotics, mainly through a defect in the response to oxidative stress. In ΔarcR mutant, the expression of the major catalase gene katA was downregulated, and katA overexpression restored bacterial resistance to oxidative stress and antibiotics. We showed that ArcR directly regulated katA transcription by binding to the promoter region of katA. Therefore, our results revealed the role of ArcR in bacterial tolerance to oxidative stress and subsequently to fluoroquinolones antibiotics.